What causes keratoconus? - Sugar, Joel; Macsai, Marian S (Cornea, 2012)
The etiology of keratoconus has been the subject of numerous studies. Here, we review the body of literature that attempts to determine what causes keratoconus. A review of the published literature was performed to evaluate the possible causes of keratoconus and how the different etiologies may play a role in the development of this disease. Peer-reviewed published papers and recent abstracts concerning the different etiologies of keratoconus were reviewed and discussed. Biochemical, genetic, and environmental factors are reviewed. The role of eye rubbing and atopic disease are explored. We agree with the hypothesis that there is a genetic predisposition that requires a "second hit" or environmental event to elicit progressive disease in keratoconus. Eye rubbing may serve as the "second hit" in some predisposed individuals. Inflammatory mediator studies question if keratoconus is really a noninflammatory thinning disorder of the cornea.